AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS EKSTRAK AIR DAN ETANOL DAUN BENALU (Dendrophthoe pentandra L. Miq) YANG TUMBUH PADA BERBAGAI INANG - Nina Artanti; Retno Widayati; Sofa Fajriah (Research Center for Chemistry - LIPI, 2009)
Mistletoes are used traditionally in Indonesiaas medicinal plant, one of this as anticancer. Cancer isone of degenerative diseases could be triggered by toomuch free radicals in the body, whereas antioxidantcould reduced the risk of degenerative diseases.Mistletoes reposted content flavonoids which known have antioxidant activity. Mistletoe potency as drugmaterial should be studied sa the utilization ofmistletoe could be developed. Antioxidant activitytest using